1988
DOI: 10.1063/1.100573
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic analysis of electronically excited species in XeCl excimer laser-induced plasmas from the ablated high-temperature superconductor YBa2Cu3O7

Abstract: Optical spectroscopic analyses have been performed to study luminescence from plasmas produced by ablation of YBa2Cu3O7 single-phase high Tc bulk superconductors exposed to XeCl excimer laser (308 nm) pulses. Only excited atomic neutral and single ionized species (Cu/Cu+, Ba/Ba+, Y/Y+) were observed within the experimental resolution of an optical multichannel analyzer detection system, when irradiating the targets in vacuum (∼10−5–10−4 Torr). Conspicuously absent in the spectra (300–800 nm range) are molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…Collected spectra has consistently identified yttrium and barium neutrals and ions, and copper neutrals. [10,19,27,39,88,90,91] However, there is disagreement with detection of copper ion emission, with some authors reporting ion emission is not present [27,39,91], while at least one group reported copper ion emission. [10] Also of significant interest is the formation and detection of oxides in the plume.…”
Section: Pulsed Laser Deposition Diagnosticsmentioning
confidence: 91%
See 2 more Smart Citations
“…Collected spectra has consistently identified yttrium and barium neutrals and ions, and copper neutrals. [10,19,27,39,88,90,91] However, there is disagreement with detection of copper ion emission, with some authors reporting ion emission is not present [27,39,91], while at least one group reported copper ion emission. [10] Also of significant interest is the formation and detection of oxides in the plume.…”
Section: Pulsed Laser Deposition Diagnosticsmentioning
confidence: 91%
“…[9] Early papers in the literature on the topic of electronic state distributions tended to take simple approaches using sparse data sets, and presented limited detail. An example of this approach is seen in Dyer [27], which reported an electronic temperature for the plume based upon the intensity ratio of two yttrium ion lines in a narrow A similar approach to Dyer was taken by Auciello [10], where spectra was collected over the 320 -830 nm wavelength range. Thirty unambiguous emission lines were assigned to specific transitions.…”
Section: Pulsed Laser Deposition Diagnosticsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] The evaporated plasma plume contains ionized atoms and molecules, neutrals and electrons, and the kinetics of the plasma plume will have a direct influence on the structural and physical properties of a deposited film. To better understand these plasma properties, a range of plasma analytical techniques such as Langmuir probe, 4-10 plasma imaging, [11][12][13][14] emission spectroscopy, [15][16][17][18][19][20] and mass spectrometry [21][22][23][24][25][26] have been used also in a number of combinations to cover different aspects and properties of plasma species. 27,28 For example, Geohegan and Puretzky investigated the laser ablation plume thermalization dynamics in background gases thereby combining optical absorption and emission spectroscopy, imaging and ion probe analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The emission spectra obtained from a multicomponent YBa 2 Cu 3 O 7 target show numerous emission lines and bands corresponding to neutral particles, ions and diatomic molecules. The dynamics of the laser-ablated YBa 2 Cu 3 O 7 plume has been studied by various techniques such as optical emission spectroscopy [5][6][7][8][9], streak photography [10,11], optical absorption spectroscopy [12][13][14], * Present Address: Department of Physics, Sree Narayana College, Punalur 691 305, India * * E-mail: root@cochin.ernet.in optical time-of-flight measurements in the nanosecond timescale range [15][16][17][18][19], interferometry [20], and laser-induced fluorescence [21]. However, most of them have been aimed at identification of ablated species and on the evaluation of their velocity distributions.…”
mentioning
confidence: 99%